Integrasi Materi Literasi Digital “Tular Nalar” dalam Perkuliahan Bahasa Indonesia - Yohanes Adven Sarbani (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This research seeks to find ways to integrate digital literacy material «Tular Nalar» in Indonesian language lectures, as well as find out student responses to digital literacy learning in Indonesian language lectures. The subjects of this study were students taking the Indonesian language course at Widya Mandala Catholic University Surabaya in the odd semester of 2021/2022. They consisted of 85% of Psychology Study Program students, 13.4% of D-III Office Administration Study Program students, and 10.7% of Philosophy Study Program students. As well as indicators of student performance, students are able to identify various types of paragraphs based on the content and location of the topic sentence. The «Tular Nalar» curriculum material is integrated as reading material for students to achieve the learning objectives of the course. After students get an explanation of the target paragraphs in the CMPK sub-group, students open the website www.tularnalar.id and enter online learning. Students read digital literacy themes in accordance with the distribution of predetermined theme readings. Student responses regarding the digital literacy material «Tular Reason» are as follows. Abstrak. Penelitian ini berusaha untuk menemukan cara mengintegrasikan materi literasi digital «Tular Nalar» dalam perkuliahan Bahasa Indonesia, serta mengetahui tanggapan mahasiswa terhadap pembelajaran literasi digital dalam perkuliahan Bahasa Indonesia. Subjek penelitian ini adalah mahasiswa yang mengikuti mata kuliah Bahasa Indonesia di Universitas Katolik Widya Mandala Surabaya pada semester gasal 2021/2022. Mereka terdiri dari 85% mahasiswa Prodi Psikologi, 13.4% mahasiswa Prodi Administrasi Perkantoran D-III, dan 10.7% mahasiswa Prodi Ilmu Filsafat. Serta indikator kinerja pembelajarnya ialah mahasiswa mampu mengidentifikasi beragam jenis paragraf berdasarkan isi dan letak kalimat topik. Materi kurikulum «Tular Nalar» diintegrasikan sebagai bahan bacaan bagi mahasiswa untuk mencapai tujuan pembelajaran mata kuliah. Setelah mahasiswa mendapatkan penjelasan mengenai paragraf sesuai target dalam sub-CMPK, maka mahasiswa membuka situs www.tularnalar.id dan masuk ke belajar online. Mahasiswa membaca tema literasi digital sesuai dengan pembagian bacaan tema yang sudah ditentukan. Tanggapan mahasiswa terkait materi literasi digital «Tular Nalar» adalah sebagai berikut ini.